The social perceptions of competency approach in the university professor - MENAI, Sana; KHELASSI, Mourad (Journal of Human Sciences, 2020)
The purpose of this study was to identify the content of the social perception of the competency approach among university teachers in the form of opinions, beliefs, ideas and attitudes. The hypothesis of this study was: The nature of the perception of skills among university teachers is negative. Twenty teachers from the University of Guelma were the sample of this study and the results were as follows: The Perception of University Teachers with Respect to the KnowledgeBased Approach, Scientific Information, and Negative Ideas that Inspire Prejudices Arising from the Cultural and Social  Environment.